P300 Importance of direct microscopy in respiratory mold infection: a diagnostic dilemma. (20th September 2022) - Tilak, Ragini; Gupta, Munesh Kumar; Narwade, Prity; Bhatia, Mohit
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM: Introduction: Opportunistic fungal infections are on the rise due to a changing healthcare paradigm worldwide. India is the second most populated country in the world and is experiencing an upward trend in fungal lung diseases. Objective: Rapid diagnosis of respiratory mold infections by direct microscopy. Material and Methods: We retrospectively analyzed the mycology of the received respiratory samples; sputum, BAL, or ETT secretion between January 1, 2021 to March 31, 2022. All the samples were processed as per standard mycological procedures. For each sample, two KOH wet mounts were prepared and examined. Samples were inoculated over SDA and blood agar and incubated at 28 °0 C and 37 ° C in BOD. Once there was growth, it was processed as per standard protocol. Results: We received a total of 109 respiratory samples from suspected respiratory fungal infections of which early morning sputum samples 84 (77%) were the predominant followed by BAL samples 25 (23%). Most of the enrolled patients were male 73(67%) with a mean age of 48 years. Among 109 samples, 83 (76%) were shown to be fungal elements by KOH wet mount while 26 (24%) were KOH negative. A total of 53 (48.6%) samples were culture-positive Aspergillus flavus 30(27%), was found to be the most common species isolated followed by A. fumigatus 16 (14.6%), miscellaneous11(10%), Aspergillus. species 5 (4.5%), and A. terreus 2 (1.8%). Conclusion: Considering the findings of KOH mount in our study, we would like to emphasize that this is a very simple, rapid, and cost-effective laboratory method with high diagnostic sensitivity when correlated with clinical findings, radiological findings, and host factors. Further, it has been found to be very dependable for making decisions to start empirical antifungal therapy early by clinicians.